A Phytogeographic Divide Along the 500 mm Isohyet in the Qinghai-Tibet Plateau: Insights From the Phylogeographic Evidence of Chinese Alliums (Amaryllidaceae) - Li, MinJie; Xie, DengFeng; Xie, Chuan; Deng, YiQi; Zhong, Yan; Yu, Yan; He, XingJin (Frontiers in Plant Science, 2019)
The Qinghai-Tibet Plateau (QTP) has been biogeographically divided into the eastern monsoonal and the western continental climatic zones along the 500 mm isohyet. However, this biogeographic hypothesis has been rarely tested using a phylogeographic approach. The members of the genus Allium subgenus Cyathophora coincidentally distribute across this biogeographical divide. Intriguingly, Allium fasciculatum of subgenus Amerallium co-occurs in the distribution range of subgenus Cyathophora. To illuminate the role of this biogeographic divide on the genetic divergence, we genotyped 466 individuals of 52 populations of subgenus Cyathophora and 110 individuals of 19 populations of A. fasciculatum using three chloroplast DNA fragments, whole nrITS and 9 nuclear microsatellite loci, supplemented with the present environmental space and paleo-distribution modeling. Our phylogeographical evidence recovered the concordant east-west genetic breaks both for subgenus Cyathophora and A. fasciculatum along the 500 mm isohyet. The divergence time estimations and environmental niche differentiations suggested this east-west genetic breaks could have been triggered by the climatic-induced vicariance during the early Pleistocene. Noticeably, this split within subgenus Cyathophora could have been deepened by the morphological vicariance from the eastern umbel to the western spicate, while that within A. fasciculatum could have been obscured due to the pollen flows from the east to west caused by the postglacial expansion. The genetic structures and ENMs recovered the distinct responses to the Quaternary climatic oscillations for species constricted to different climatic zones, further highlighting the profound effect of the climatic differences and tectonic uplifts on the genetic diversification. Overall, our findings offer strong evidence for the existence of a biogeographic divide between the eastern monsoonal and the west continental climatic zones of the QTP nearly along the 500 mm isohyet.